Atomização por spray dryer dos extratos de aspidosperma pyrifolium e aspidosperma macrocarpum - Azevedo, Erlan Pereira de (2013)
Plants species Aspidosperma pyrifolium Mart., popularly knowned as “pereiro preto” or “pereiro do sertão” and Aspidosperma macrocarpum Mart., knowned as “guatambu”, “peroba-cetim”, both belonging to Apocynaceae family. Scientific studies demonstrates that, through another activities, A. pyrifolium’s extracts showed activity against Bacillus subtilis, besides antiplasmodial activity due the isolated alkaloids. Whilst extracts of A. macrocarpum showed antimalarial activity. However, in reference literature, was not found any data about the development of dry extracts from these plants species. The A. macrocarpum leaves and A. pyrifolia bark collected, submitted to a drying process in greenhouse and crushed. For percolation process, a hydroalcoholic extract was obtained using 90% ethanol as solvent. The crude extract was subjected to the process of spray dryer. Colloidal silicon dioxide was used as adjuvant in process a concentration of 10%, obtaining a yield of 48.6% and 77.6% for A. pyrifolium and A. macrocarpum respectively. The infrared spectroscopy was performed with the crude extract and extract atomized obtaining the same spectroscopic profile was found in two forms analyzed. Through thermogravimetric analysis has showed that the thermal stability of the samples, as well the low moisture content below 10%, as confirmed by Karl Fischer method and loss on drying. Photomicrographs obtained by Scanning Electron Microscopy (SEM) showed that the particles of both species obtained after drying feature semi-spherical shape and did not show the presence of fractures on its surface. Moreover, both the crude extract as atomized demonstrated antioxidant activity. Thus, the production of extracts dried by spray drying, using as starting material the extracts of A. pyrifolium and A. macrocarpum shown to be a promising alternative for obtaining the powder as an intermediate.